Extension of shelf life of two fatty foods using a new antioxidant multilayer packaging containing green tea extract. (February 2016) - Carrizo, Daniel; Taborda, Gonzalo; Nerín, Cristina; Bosetti, Osvaldo
Abstract: The performance of an antioxidant multilayer packaging containing green tea extract was studied over a long-term experiment with real commercial food. Two types of food (dark chocolate peanuts and milk chocolate cereals) were packaged and tested during 16 months. Antioxidant performance of the multilayer packaging was demonstrated. Volatile profile (hexanal, pyrazines and related compounds) and fatty acids were used as indicators to monitor the system performance. The volatile compounds wereanalyzed monthly, identified and quantified by HS-SPME-GC-MS, while the fatty acids were analyzed after derivatization by GC-MS every 3 months. Significant lower values of hexanal were obtained for the active system during the time experiment while the values for the fatty acids were higher in the active system compared to the non-active one. Organoleptic tests carried out with a trained panel confirmed the antioxidant effect. The radical scavenger capacity of the multilayer was also quantitatively evaluated. The new approach of antioxidant behavior as a radical scavenger of green tea is discussed in detail. Industrial relevance: This paper describes the performance of a new antioxidant multilayer packaging material, tested for 16 months with real food and in industrial conditions, as the format, size and material were produced at an industrial level, as a new prototype, following the indications from previous research. In this material green tea extract has been grafted in the internal layer of a multilayer material, in which it acts as a radical scavenger, which means as an antioxidant. The antioxidant behavior of the polymer as well as the performance of the polymer versus real food is described. It is the first time that such a material is successfully produced at the industrial level and in fact, the material is nowadays in the market. For all these reasons the paper is of great industrial relevance. Many industries are and will be interested in it. HIghlights: Two real foodstuffs have been tested with a new antioxidant packaging. Volatile and fatty acid profiles were monitored for 16 months. Multilayer packaging contained green tea extract (GTE) as an antioxidant. Real free radical scavenger of GTE has been demonstrated Active packaging protected both foods against oxidation processes.